Minoxidil Solid Dispersion Tablets: A Strategy for Accelerated Onset and Improved Drug Delivery - Dushyant; Balram; Jangra, Geeta; Singh, Gurvirender; Narwal, Smita; Devi, Rupa; Dhingra, Ashwani K.; Kumar, Nitish (Drug Delivery Letters, 2025)
<span class=
Keywords: minoxidil